Synthesis of Some New Phenolic Azo Schiff Bases-Part- I - Raut, A.W.; Jadhao, S.T.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
p-Nitroaniline on diazotisation gives p-nitrobenzene diazonium chloride (I) which on condensation with salicylaldehyde gives 2-hydroxy-5-(4- nitrophenylazo) benzaldehyde (II). The compound (II) on condensation with substituted aniline gives 2-hydroxy-5-(4-nitrophenyl azo) benzylidine substituted aniline, i.e., substituted phenolic azo Schiff bases.